2014
DOI: 10.3892/mmr.2014.2011
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-125b promotes leukemia cell resistance to daunorubicin by inhibiting apoptosis

Abstract: Abstract. microRNA-125b (miR-125b) is overexpressed in several types of cancer and contributes to tumor resistance to chemotherapy. The present study investigated the effect of miR-125b on the resistance of leukemia cell lines to the chemotherapeutic agent daunorubicin (DNR). miR-125b expression was found to be upregulated in patients who had failed therapy compared with those who demonstrated event-free survival. The overexpression of miR-125b was observed to induce DNR resistance in K562, THP-1 and Jurkat ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
2
22
0
2
Order By: Relevance
“…Another report from the same group showed that overexpression of Snail in breast cancer cells dramatically increases the expression of miR-125b through the Snail-activated Wnt/β-catenin/TCF4 axis 18. Moreover, miR-125b was also shown to be involved in chemotherapy resistance in other caners 19, 20. For example, miR-125b promoted leukemia cell resistance to daunorubicin (an anthracycline family member) by inhibiting apoptosis 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report from the same group showed that overexpression of Snail in breast cancer cells dramatically increases the expression of miR-125b through the Snail-activated Wnt/β-catenin/TCF4 axis 18. Moreover, miR-125b was also shown to be involved in chemotherapy resistance in other caners 19, 20. For example, miR-125b promoted leukemia cell resistance to daunorubicin (an anthracycline family member) by inhibiting apoptosis 20.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-125b was also shown to be involved in chemotherapy resistance in other caners 19, 20. For example, miR-125b promoted leukemia cell resistance to daunorubicin (an anthracycline family member) by inhibiting apoptosis 20. On the other hand, miR-141 is overexpressed in cisplatin resistant ovarian, gastric and esophageal squamous cancer cells by targeting KEAP1 and YAP1 21-23.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, overexpression of miR-125b caused a significant increase in IC 50 of both drugs, thereby confirming its role in development of therapeutic resistance. These data were subsequently corroborated in a cohort of 46 acute leukemia patients [37]. Again, high miR-125b expression was observed and associated with decreased event-free survival (EFS).…”
Section: Mirnas and Lncrnas In Sensitivity And Resistance To High-mentioning
confidence: 65%
“…Although the use of cell lines has led to the identification of a number of dysregulated miRNAs involved in apoptosis and/or leukemiagenesis (Li et al, 2013; Yamada et al, 2014; Zhou et al, 2014; Fan et al, 2016), cellular heterogeneity associated with cancerous tissues require careful interpretation of the data acquired from human studies. Cellular heterogeneity is also an important issue that needs to be taken into account while interpreting the data collected from cell lines.…”
Section: Introductionmentioning
confidence: 99%